Maintenance of Facilities and Infrastructure in SMK Negeri 7 Padang - Setia Ningsih, Tiara; Sulastri; Hadiyanto; Yulianto Santoso (Journal of Practice Learning and Educational Development, 2024)
This research is motivated by maintenance related to the maintenance of facilities and infrastructure which is not yet optimal, as can be seen from several phenomena that have emerged. This research aims to find out how to maintain facilities and infrastructure routinely, how to maintain facilities and infrastructure in a preventive manner, how to monitor the maintenance of facilities and infrastructure and how to monitor the maintenance of facilities and infrastructure at SMK Negeri 7 Padang. The method used in this research is a descriptive qualitative method. The data collection technique uses snowball sampling technique with observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Data validitytechniques use triangulation techniques to get more effective and accurate results. The informants in this research consisted of the Head of Facilities and Infrastructure, teachers, students, school officers and school guards. The research results obtained in research related to the maintenance of facilities and infrastructure at SMK Negeri 7 Padang include: 1) continuous maintenance of facilities and infrastructure by planning, 2) preventative maintenance of facilities and infrastructure carried out with certain criteria, 3) maintenance supervision facilities and infrastructure carried out by the school principal, deputy head of school facilities and infrastructure and facilities and infrastructure coordinator, 4) efforts to supervise the maintenance of facilities and infrastructure by carrying out direct supervision in the field